The Background of the Myanmar Conflict - Sopyani, Indah (Peneliti.net, 2025)
The conflict in Myanmar, especially related to the Rohingya crisis and internal ethnic conflicts, has caused serious humanitarian impacts. Indonesia's role in dealing with the Myanmar conflict involves diplomacy, humanitarian assistance, and advocacy efforts. Various efforts and cooperation continue to be carried out to deal with the human crisis that is occurring in Myanmar. In this journal, researchers will briefly examine the background of the conflict in Myanmar and Indonesia's role in working with Myanmar to ease this conflict.